The Principles of the Jesuitic Spiritual Education in Meditations (1650) by Nicolaus Lancicius - Čitavičiūtė, Dovilė (Senoji Lietuvos literatūra, 2017)
This paper deals with the book of Meditations (Meditationes nova et absolutissima methodo pro maiori meditantium commoditate digestae […], in: Nicolai Lancicii e Societate Jesu Opusculorum spiritualium tomus secundus, Antuerpiae: Apud Iacobum Meursium, 1650) by Nicolaus Lancicius, a prominent Polish-Lithuanian Jesuit. It is one of the early examples of the Jesuit devotional literature in the Polish-Lithuanian Commonwealth. It is obvious that Loyola’s Spiritual Exercises were the model for Lancicius’s Meditations. This article compares their approach to prayer and the contexts of their use in an attempt to delineate the subtle changes in the application of the Jesuitic spiritual education that took place by the mid-seventeenth century. There are obvious differences in the structure and intent: Exercises were conceived as a four-week retreat with the aim of making an important life decision, while Meditations cover, both temporally and thematically, the span of the entire liturgical year and are intended as a tool of spiritual and theological education, primarily for Jesuit novices. Both Lancicius and Loyola see meditating as a prayer technique that liberates the praying from the written text of the New Testament. Reading is substituted with imagination, as the object of meditation is a mental image constructed according to the readable (or, indeed, audible) instructions. Both Jesuits emphasize the need to aspire to (moral) perfection, the imperative to cultivate virtue, and one’s personal connection to God. In Meditations, these are achieved through the application of the exercises conceived by Loyola himself: the examination of conscience, the second mode of prayer (contemplating a sacred text word by word), and meditation. They are freely rearranged by Lancicius into new units, involving and developing, at different times, one’s imagination, cogitation, memory, willpower, and feeling capacities. In this respect, Lancicius’s Meditations is the exercise prior to Loyola’s Exercises, familiarizing the Jesuit novices with the techniques of Ignatian prayer and helping them develop a deeply personal approach to the New Testament and the liturgy.